"Pathological Gamblers" and "Sovereign Consumers": National Gambling Regulation and the Challenges of European Integration and Digitization in Germany, 2004–2018. Issue 1 (March 2022) - Kaiser, Laura
Abstract: This study examines the interrelationship between national sovereignty and individual consumer sovereignty in the age of a global liberal economy and digital markets by analyzing Germany's gambling regulations. As gambling policies were codified and liberalized from 2004 to 2018, gambling addiction quickly became the key issue in legal and political quarrels over regulation. The article will shed light on the differing interests at play in the controversy and discuss how discourses on addictive gambling behavior affected political disputes over gambling liberalization. It explores contemporary German gambling regulations in the context of European integration and the digitization of the gambling market, which posed crucial challenges to national sovereignty. I argue that Germany's claim for national autonomy over gambling regulations was deeply intertwined with the question of individual consumer sovereignty because it relied on the pathologization of certain types of gambling consumption and gamblers. The emergence of the "pathological gambler" can be understood as the manifestation of a new socioeconomic and political order in which risks emanating from liberalized markets are dealt with as individual consumer addiction issues.